Multi-attribute decision-making problem using complex q-rung orthopair fuzzy interaction aggregation operators - Khan Z.; Ullah I.; Hussain F.; Rahim T.; Jan R.; Khan M. (Springer Nature, 2025)
The complex q-rung orthopair fuzzy sets are an important way to express uncertain and ambiguous information, and they are superior to the complex fuzzy sets, complex intuitionistic fuzzy sets, complex pythagorean fuzzy sets, and complex fermatean fuzzy sets. This paper extend the notion of q-rung orthopair fuzzy sets to complex q-rung orthopair fuzzy sets. Interaction aggregation operators are often used in various fields to solve multi-attribute decision-making Problems. By utilizing arithmetic and geometric operators, some well-known complex q-rung orthopair fuzzy interaction aggregation operators such as complex q-rung orthopair fuzzy interaction weighted average operator, complex q-rung orthopair fuzzy interaction weighted geometric operator, complex q-rung orthopair fuzzy interaction order weighted operator, complex q-rung orthopair fuzzy interaction order weighted geometric operator, complex q-rung orthopair fuzzy interaction hybrid operator, and complex q-rung orthopair fuzzy interaction hybrid geometric operator have been developed. In addition, some of the unique properties of these newly established operators are investigated. Finally, we explore a decision-making approach to solve multi-attribute decision-making Problem. The viability and flexibility of the suggested technique is explored with the help of a numerical example and the proposed results are compared with several existing approaches. ? The Author(s) under exclusive licence to Korean Society for Informatics and Computational Applied Mathematics 2024.